Development of a literacy pocket book based on Tri-N teachings to strengthen the profile of Pancasila students in the critical reasoning dimension of elementary school students - Purwati, Purwati; Nisa, Ana Fitrotun (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study is (1) to describe the analysis of the needs of literacy pocket books based on Tri-N teachings to improve critical reasoning dimensions. (2) to describe the results of the validity of the pocket book product. (3) to describe the results of the pocket book effectiveness test. This study is used as a solution to improve students' critical reasoning. This study is a Research and Development (RnD) research and development with the ADDIE model (analyze, design, development, implementation, and evaluation). The trial subjects were grade VI students of SDN Paliyan I with 7 students and a large-scale trial class at SDN Paliyan II totaling 18 students. Data collection techniques used observation and interview methods while data analysis techniques used questionnaires and validation sheets.The results of this development research are (1) Characteristics of pocket book development in niteni, nirokke, and nambahi activities. (2) Product feasibility based on validity tests according to learning resource validators showed a score of 80% and media experts showed a score of 85% or in the very valid category. (3) The effectiveness of the pocket book product is proven by the results of observations that show an average value before using the pocket book of 4.57 and after using the pocket book of 8.57 with an average N Gain score calculation of 0.74 or a high category. While on a broad scale the average is 0.71 or a high category. This shows that Tri-N based pocket books are able to improve critical reasoning characters through literacy activities.